Disparities in Knowledge of Mouth or Throat Cancer Among Rural Floridians. Issue 3 (22nd February 2013) - Riley, Joseph L.; Pomery, Elizabeth A.; Dodd, Virginia J.; Muller, Keith E.; Guo, Yi; Logan, Henrietta L.
Abstract Objective The aim of this study was to examine risk factors for reduced mouth or throat cancer (MTC) knowledge using a sample of rural North Floridian adults. Methods Telephone interviews were conducted across rural census tracts throughout North Florida in 2009‐2010, using a survey adapted for cultural appropriateness. The sample consisted of 2, 393 individuals (1, 059 males and 1, 334 females; 1, 681 whites and 712 blacks). Findings Only 9% of the study respondents indicated they had not heard of MTC; however, only 12% endorsed knowing "a lot." Higher education levels and health literacy indicated they had more MTC knowledge. Among female participants, whites had more knowledge than blacks (OR = 1.9). Among black participants, males had more knowledge than females (OR = 1.7). Conversely, greater concern with MTC was associated with lower education levels, health literacy, and financial status, but higher depression scores. Awareness that excessive sun exposure is a risk factor for MTC was lower than for earlier studies using more urban samples. Conclusions This study adds to the literature on MTC knowledge and concern because this sample was drawn exclusively from rural populations in North Florida, a group with the highest MTC morbidity and mortality. An unanticipated finding was that blacks were more concerned than their white rural counterparts. This study was also the first to report that depression was associated with increased concern about MTC. The goal is to persuade at‐risk groups to obtain MTC screenings with the goal of reducing disparities in MTC whenever they occur.